THE STRUCTURE AND PROFITABILITY OF WHOLESALE MARKETING OF COCOYAM IN SOUTHEAST, NIGERIA - Eucharia C, Nwankwo; C.O, Ugwumba,; Njideka Rita, Chiekezie; Maurice Uche , Ozor, (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2023)
Wholesale marketing plays an important role in improving agricultural marketing efficiency, developing rural economy and promoting the process of agricultural modernization. To this extent, wholesaling tries to close the gap in supply chain between surplus (production site) and deficit areas (urban areas). Using cocoyam wholesale marketing, the study tends to examine how structure and profitability of the market contribute to the product availability, price formation and rural economic growth. The study employed multistage, purposive and random sampling techniques to generate relevant data using a structured questionnaire administered to 216 cocoyam wholesale marketers in eighteen markets in three states of the southeast (Anambra, Enugu and Imo). Herfindahl Index (HI) and Gini Coefficient (GC) were used to determine the market concentration or nature of competition in the market i.e. market structure; descriptive statistics was used to determine market conduct and enterprise budgeting analysis was used to analyse the profitability . Gini Coefficient value of 0.5642 indicated an oligopolistic market structure, implying that greater portion of market revenue is concentrated in the hands of few wholesale marketers and HHI with the value of 0.14, implied a low degree of inequality among the wholesale marketers. Findings on the market conduct revealed that prices of cocoyam in the market were mostly fixed based on bargaining power of the marketers (61.1%). The variance in the selling price among the marketers also suggested that the marketers have some level of control over the price of their products though associations influence the price determination in some areas. Net return on investment indicated that wholesale cocoyam marketing returned 35 kobo for every ?1.00 invested which is an indication of a profitable business venture.